Karakteristik Pengendara Sepeda Motor Dan Penggunaan Helm Di Kampus Universitas Riau - Taufik, Hendra; Warningsih, Trisla (SAINSTEK, 2024)
A helmet is one of the pieces of equipment that must be carried when riding a motorbike. Helmets can function to protect head injuries when accidents occur on the road. This research aims to determine the characteristics and opportunities for wearing helmets for new students at Riau University. Data on helmet use was obtained from distributing questionnaires to new students via Google Form who pass through campus almost every day to study. This research uses descriptive analysis and multiple regression analysis methods. From the research results, the number of respondents was 452 respondents. From the number of respondents, 322 respondents were found to use two-wheeled vehicles. Based on the characteristics of motorcyclists, there are 6 variables that have a relationship with helmet use, namely: SNI helmets, reasons for using helmets, passenger capacity, traffic compliance, helmet straps and gender. The variables that most influence the use of helmets are gender, namely 86%, traffic compliance at 57.13%, use of helmet straps at 49.47%, the main reason for using SNI helmets with an influence level of 47.46% and passenger capacity of more than 1 people namely 30.24%